If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -5) + 6(3 + -1x) = 5x + -13w Reorder the terms: 3(-5 + x) + 6(3 + -1x) = 5x + -13w (-5 * 3 + x * 3) + 6(3 + -1x) = 5x + -13w (-15 + 3x) + 6(3 + -1x) = 5x + -13w -15 + 3x + (3 * 6 + -1x * 6) = 5x + -13w -15 + 3x + (18 + -6x) = 5x + -13w Reorder the terms: -15 + 18 + 3x + -6x = 5x + -13w Combine like terms: -15 + 18 = 3 3 + 3x + -6x = 5x + -13w Combine like terms: 3x + -6x = -3x 3 + -3x = 5x + -13w Reorder the terms: 3 + -3x = -13w + 5x Solving 3 + -3x = -13w + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 3 + -3x + -5x = -13w + 5x + -5x Combine like terms: -3x + -5x = -8x 3 + -8x = -13w + 5x + -5x Combine like terms: 5x + -5x = 0 3 + -8x = -13w + 0 3 + -8x = -13w Add '-3' to each side of the equation. 3 + -3 + -8x = -3 + -13w Combine like terms: 3 + -3 = 0 0 + -8x = -3 + -13w -8x = -3 + -13w Divide each side by '-8'. x = 0.375 + 1.625w Simplifying x = 0.375 + 1.625w
| 8+5=213 | | -15=-n+6n | | 2y=8-9x | | 6x^3+30x^2+7x+35=0 | | 75+2x=180 | | -2x-10+4x+25=-2 | | x=-20+3X | | 2(4f+2g)2=8f+2g | | -5x+8+7x=6 | | 2(4f+2g)2=2f(4+2g) | | 3=3tx-5x | | cos(x)+cos(3x)=2sen(6x)cos(x) | | -4=-2(8x-12) | | 3=3t*-5x | | cos(x)+cos(3x)= | | Y-14=4(x-2) | | b=(3.14)(12)2 | | 5x*5x-15x-50=0 | | s*5-22=98 | | 5w-11=89 | | 9x-2=5x+8 | | 5x-10xy=5(x-2y) | | 5x-4=10y | | 2x+9=5x+54 | | 2x+15=x+16 | | 5/9+2/9= | | -6-2(m+4)=36 | | 3y-11=2y-6 | | 4x-5(2x+1)=7x+3(4x-5) | | 3/2-2/7= | | x+x+x+2=3+2x | | 4.9-5.2=4.7 |